2015
DOI: 10.1007/s10393-015-1034-3
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Demographic and Environmental Variables Correlated with Lyme Disease Emergence in Virginia

Abstract: Lyme disease is the United States' most significant vector-borne illness. Virginia, on the southern edge of the disease's currently expanding range, has experienced an increase in Lyme disease both spatially and temporally, with steadily increasing rates over the past decade and disease spread from the northern to the southwestern part of the state. This study used a Geographic Information System and a spatial Poisson regression model to examine correlations between demographic and land cover variables, and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 28 publications
9
42
2
Order By: Relevance
“…In our study, the forest fragment perimeters (FragPerim06) is not included in the final models for either ecoregions. Seukep et al (2015) found that the percentage of forest was not selected, while our findings support the results in Jackson, Hilborn, and Thomas (2006) and suggest that it is an important variable. Seukep et al (2015) fitted a spatial model using Lyme disease data without considering the ecoregion variable.…”
Section: Virginia Lyme Disease Data Analysissupporting
confidence: 82%
“…In our study, the forest fragment perimeters (FragPerim06) is not included in the final models for either ecoregions. Seukep et al (2015) found that the percentage of forest was not selected, while our findings support the results in Jackson, Hilborn, and Thomas (2006) and suggest that it is an important variable. Seukep et al (2015) fitted a spatial model using Lyme disease data without considering the ecoregion variable.…”
Section: Virginia Lyme Disease Data Analysissupporting
confidence: 82%
“…, Seukep et al. ). However, unlike forest fragmentation resulting from human development (Allan et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Seukep et al. ) or sudden oak death (Swei et al. , ), destruction of forested habitats by wildfire is much more sudden and catastrophic, which may have very different effects on the ecology of tick‐borne disease.…”
Section: Discussionmentioning
confidence: 99%
“…One of our next undertakings in our Lyme disease research in Virginia is to use environmental data and population data to build a model relating Lyme disease occurrence and environmental and demographic variables. 12 This analysis will help us to identify the factors that affect Lyme disease infection risk, explain patterns of Lyme disease spread noted in this study, and provide better guidance to public health practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Statewide surveillance for Lyme disease in Virginia started in 1989 when it became a reportable disease. 12 This study examined all Lyme disease-positive laboratory reports received by the VDH for patients from commercial testing laboratories as well as Lyme disease case reports provided to the VDH by physicians as part of Virginia's Lyme disease case surveillance. Lyme case classification at the VDH was based on the National Surveillance Case Definition for Lyme disease.…”
Section: Methodsmentioning
confidence: 99%